Pedagang Kuliner Kawasan Wisata Tanggo Rajo Ancol Jambi 1960 an – 2015 - Putri Pramayanti, Ade; Heidi Karmela, Siti; Hariadi, Ujang (Universitas Batanghari Jambi, 2023)
This research is historical research with the theme of economic history with the object ofresearch being culinary traders in the Tanggo Rajo Ancol Tourism Area, Jambi from the 1960s– 2015. The purpose of the research is to provide information about the existence of the AncolTourism Area as a center for culinary tourism in Jambi City. from the emergence, development,and management in accordance with the research periodization. Next, it will explain theeconomic conditions of the culinary traders who sell there and the effect of the area on theincome of culinary traders.The method used is the historical method starting from the stagesof heuristics, criticism, interpretation, and historiography. The theory that fits this research isthe Multiplier Effect. In the end, the findings obtained after conducting field research showedthat culinary traders in the Tanggo Rajo Ancol Tourism Area, Jambi, had been selling fordecades before the area was known as a tourist area. Furthermore, it is known that the incomeof culinary traders will increase compared to their daily income if it coincides with importantmoments such as school holidays, the month of Ramadan, holidays, celebrations of theIndonesian Independence Day and Jambi Province Anniversary, and festivals with culturalnuances. Next, culinary traders in the Tanggo Rajo Ancol Jambi Tourism Area areconcentrated in two locations, namely under the Gentala Arasy Bridge to the Tanggo RajoGate and from the Jambi Police Chief's House to Kasang Harbor / Pasir Harbor.